P216 WHAT IS THE TIME BURDEN AND RESPONSE RATE ASSOCIATED WITH WRITTEN OR ONLINE COMPLETION OF HEALTH-RELATED QUALITY OF LIFE QUESTIONNAIRES AFTER CANCER TREATMENT?. (23rd November 2019) - Klevebro, F; Boshier, P; Jenq, W; Low, D
Abstract: Background: Patient reported outcomes are increasingly important assessments to be applied in the follow-up of patients after cancer treatment. The primary aim of this study was to clarify the patient related time burden associated with completing these questionnaires. Secondary aims was to assess completion rates, and to investigate how symptomatic outcome differs according to the response time. Method: Patients who had undergone surgical management of esophageal cancer (1991-2018) and were disease-free at the time of assessment were asked to complete a total of six questionnaires: SF36, EORTC-QLQ-C30, EORTC-QLQ-OG25, EuroQol 5D, Digestive Symptom Questionnaire, and Dumping Syndrome Rating Scale. Patients were offered either paper or online questionnaires that were completed consecutively allowing for accurate quantification of the time taken to complete each online questionnaire. Results: In total, 117 of 147 eligible patients (79.6%) responded to the questionnaires. In the online group 60 (90.9%) responded compared to 57 (70.4%) in the paper group (P=0.002). The median age was 74.5 years in the online group compared to 70.9 years in the paper group (P=0.022). In the patients completing their questionnaires online, the six questionnaires took on average 26.4 (range 10-55) minutes to complete. The fastest quartile of patients completed the six questionnaires in 17 minutes or less (N=14). There was no significant association between time to complete the questionnaires and age, gender, time from surgery or health-related quality of life scores. Conclusions: The results of the study demonstrates that online questionnaires in some ways might be superior to paper questionnaires, and that patients are willing and able to complete online questionnaires irrespective of age. Time to complete questionnaires was not associated with level of health-related quality of life.